2014
DOI: 10.1021/jf503260v
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Related Antioxidant Properties in Differently Colored Lettuces: A Study by Electron Paramagnetic Resonance (EPR) Kinetics

Abstract: Differently colored lettuce (Lactuca sativa L.) cultivars (green, green/red, and red) were studied to correlate their phenolic composition with their antioxidant kinetic behavior. Electron paramagnetic resonance (EPR) was employed to monitor decay kinetics of 1,1-diphenyl-2-picrylhydrazyl (DPPH(•)), which allowed the identification of three differently paced antioxidants. The results showed that as long as lettuce had higher red pigmentation, the hydrophilic antioxidant capacity increased together with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
6
32
0
Order By: Relevance
“…This has been confirmed by others studies on various lettuce cultivars in which caffeic acid derivatives were identified . Our results correspond with those of Mulabagal et al and Pérez‐López et al , who noted that the most representative phenolic acid for lettuce cultivars was chicoric acid. As several previous studies indicate, the content of phenolics may be correlated with some pro‐health activity of plant food.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This has been confirmed by others studies on various lettuce cultivars in which caffeic acid derivatives were identified . Our results correspond with those of Mulabagal et al and Pérez‐López et al , who noted that the most representative phenolic acid for lettuce cultivars was chicoric acid. As several previous studies indicate, the content of phenolics may be correlated with some pro‐health activity of plant food.…”
Section: Discussionsupporting
confidence: 93%
“…Our results correspond with those of Mulabagal et al and Pérez‐López et al , who noted that the most representative phenolic acid for lettuce cultivars was chicoric acid. As several previous studies indicate, the content of phenolics may be correlated with some pro‐health activity of plant food. Our research suggests that the phenolics (especially chicoric and chlorogenic acids) induced after elicitation with yeast extracts are most likely responsible for the plant's antioxidant capacity (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between colour and antioxidant compound accumulation in plant organs has recently been documented in leaves of variously coloured lettuce varieties. 29 As long as lettuce had higher red pigmentation, contents of free and conjugated phenolic acids, free and conjugated flavonoids and anthocyanins increased, suggesting that relationships among pigments and isoflavones may occur in other plant species and organs.…”
Section: Error (%)mentioning
confidence: 99%
“…Nitrogen, which is a vital nutrient, is an extremely important factor affecting the production of phenolic compounds in plants, and a reduction in nitrogen availability generally increases the level of phenolic compounds in plants . Chemical assays, such as ABTS, DPPH and FRAP assays, are some of the most widely used methods for the evaluation of antioxidant activity in vegetables because of advantages such as low cost, as well as simple and rapid operation . Our previous study showed that lettuce cultivated with low nitrate levels exhibits a higher phenolic content, and thus, a higher DPPH radical‐scavenging capacity and FRAP value .…”
Section: Introductionmentioning
confidence: 99%